An In-Vitro Analysis of the Mechanical and Anti-Bacterial Properties of Betel Leaf Extract with Chitosan Coating on Orthodontic Aligners - Nazleen Valerie Vas; Ravindra Kumar Jain; Kumaravel Kaliaperumal (Association of Support to Oral Health Research (APESB), 2024)
Objective: To aim at the preparation and characterization of a chitosan and betel leaf extract biopolymer followed by an assessment of mechanical and antibacterial properties. Material and Methods: A chitosan-betel leaf stock solution was prepared and dip-coated on thermoformed aligner cubes. The groups (five samples per group) involved were one control (only chitosan coating) and three test groups based on the duration of coating (coating with chitosan and betel extract coated for 5, 10, and 15 minutes, named B5, B10, and B15 respectively). The coating of the samples was confirmed by an FTIR test and anti-microbial properties were assessed by the disc diffusion method. Wear resistance assessment of the coating was carried out by scratch test. Results: Coating of the aligners with the extract was confirmed with FTIR. The zone of inhibition against S. mutans was noted to be the widest for aligners coated for 15 minutes (7± 0.5mm), and the intergroup difference was statistically significant (p<0.05). The samples dip-coated for 15 minutes demonstrated the highest wear resistance (3.2 ±0.17 N) with statistically significant intergroup differences (p<0.05). Conclusion: Betel leaf extract prepared and incorporated with chitosan biopolymer was successfully coated on thermoformed aligners. A higher antibacterial activity and scratch resistance were evident with aligners dip-coated for 15 minutes, owing to the antibacterial activity of Piper betel.